The Landscape of a Religious Workspace: The Case of a Russian Christian Orthodox Sisterhood - Ксения Медведева (Социологическое обозрение, 2015)
In this article, I examine the specifics of a workspace in one of the Christian Orthodox organizations in Russia. The sisterhood which I analyze represents the interlacement of religious and economic discourses in the workplace. I discuss the “commodification” of piety which is seen as a professional competency in the labour relations among Orthodox Christians. It is true about the sisterhood, where being“inchurched” is one of the main filters for potential employees.I examine the “politics of labour” in the sisterhood through the analysis of its heterogeneous spatial composition and point at the differences between its spaces in their work tempo, prestige, and working conditions. Alongside economic goals, the sisterhood is aimed at missionary and educational work; however, commercial relations are often described using religious terminology. I discussthe conflict between religious and economic aims of work. Particular attention is given to the analysis of techniques that help to maintain discipline in the sisterhood. It is achieved through rational organization of labour, observability of the workplace, hierarchy in employer-employee relationships, and the disciplining of body and emotions. The analysis is based on the materials of participant observation and field materials collected during my four months as a staff member of the sisterhood.